Nilai Dialog Antaragama dalam Dialogue With Trypho Karya Yustinus Martir - Sihombing, Kaisar Octavianus (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2024)
Going back to the time of the Church Fathers to find a comparative perspective in interpreting interreligious dialogue is an option that cannot be ignored. Contextually, we need more historical-academic approaches to building interreligious dialogues, both internally among Christians, among adherents of Abrahamic religions, as well as more broadly among people who have interests in religion. One of the important figures in the prototype of interreligious dialogue is Justin Martyr. He was a philosopher and theologian of the second century who had intellectual and actual experience in encounters with other religions. In his Dialogue with Trypho in its Sitz im Leben, Justin Martyr emphasized the importance of philosophy in the joint search for truth and eliminating groundless stories in religion. Dialogue does not ignore orthodoxy in the faith of each believer. Dialogue invites people to be able to affirm the authenticity of the teachings of their faith and confirm them. The affirmation of the teachings of faith is conveyed with scientific background and arguments so that it can avoid ad hominem discussions. This is how Justin Martyr's writing is interpreted so that theology for dialogue and theology of dialogue are simultaneously interpreted in value.AbstrakKembali ke masa Bapa-bapa Gereja untuk menemukan perspektif pembanding dalam memaknai dialog antarumat beragama adalah sebuah opsi yang tidak bisa diabaikan. Secara kontekstual, kita membutuhkan lebih banyak pendekatan historik-akademik untuk membangun dialog-dialog interreligius, baik secara internal di antara orang Kristen, di antara penganut agama-agama abrahamik, juga secara lebih luas di antara orang-orang yang memiliki interese mengenai agama. Salah satu tokoh penting dalam prototype dialog antaragama adalah Yustinus Martir. Dia adalah seorang filsuf dan teolog dari abad kedua yang memiliki pengalaman intelektual dan aktual dalam pertemuan dengan agama lain. Dalam Dialogue with Trypho dengan Sitz im Leben-nya, Yustinus Martir menekankan pentingnya filsafat dalam pencarian bersama menuju kebenaran dan mengeliminasi groundless stories dalam agama. Dialog tidak mengabaikan ortodoksi dalam beriman oleh setiap penganutnya. Dialog mengajak orang untuk mampu menegaskan keaslian ajaran imannya dan menegaskannya. Penegasan ajaran iman itu disampaikan dengan latar belakang dan argumentasi ilmiah sehingga dapat terhindar dari perbincangan ad hominem. Demikian tulisan Yustinus Martir ini dimaknai sehingga teologi untuk dialog dan teologi dialog serentak dimaknai nilainya.